Sulphur chemistry in the L1544 pre-stellar core. Issue 4 (18th May 2018) - Vastel, Charlotte; Quénard, D; Le Gal, R; Wakelam, V; Andrianasolo, A; Caselli, P; Vidal, T; Ceccarelli, C; Lefloch, B; Bachiller, R
ABSTRACT: The L1544 pre-stellar core has been observed as part of the ASAI IRAM 30 m Large Program as well as follow-up programs. These observations have revealed the chemical richness of the earliest phases of low-mass star-forming regions. In this paper, we focus on the 21 sulphur bearing species (ions, isotopomers, and deuteration) that have been detected in this spectral-survey through 51 transitions: CS, CCS, C3 S, SO, SO2, H2 CS, OCS, HSCN, NS, HCS +, NS +, and H2 S. We also report the tentative detection (4σ level) for methyl mercaptan (CH3 SH). LTE and non-LTE radiative transfer modelling have been performed and we used the nautilus chemical code updated with the most recent chemical network for sulphur to explain our observations. From the chemical modelling, we expect a strong radial variation for the abundances of these species, which mostly are emitted in the external layer where non-thermal desorption of other species has previously been observed. We show that the chemical study cannot be compared to what has been done for the TMC-1 dark cloud, where the abundance is supposed constant along the line of sight, and conclude that a strong sulphur depletion is necessary to fully reproduce our observations of the prototypical pre-stellar core L1544.